An Analysis of the Factors Influencing Employability Skills Among Students in the Office Management Program at SMK Negeri 16 Jakarta - Rika Wardi Manihuruk; Dedi Purwana; Susan Febriantina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The high unemployment rate among vocational high school graduates indicates that the employability skills of vocational education graduates still need to be improved. This study aims to analyze the influence of soft skills, self-efficacy, digital literacy, learning motivation, career planning, and social support on the employability skills of 11th-grade Office Management students at SMK Negeri 16 Jakarta, both partially and simultaneously. The study used a quantitative approach with a saturation sampling technique, so all 71 students were included in the sample. Data were collected via an online questionnaire and analyzed using multiple linear regression with the aid of SPSS. The results indicate that, individually, soft skills, learning motivation, and career planning have a positive and significant effect on employability skills. Soft skills are the variable with the most dominant influence. Conversely, self-efficacy, digital literacy, and social support did not show a significant effect. Simultaneously, all six variables had a significant effect on employability skills with an Adjusted R-Square value of 0.433, meaning the model explains 43.3% of the variation in employability skills, while the remaining 56.7% is influenced by other factors outside the scope of this study. These findings indicate that strengthening soft skills, learning motivation, and career planning should be prioritized in enhancing the employability skills of vocational high school students.